Manifestation of Religious Moderation in Multicultural Metropolitan Community Surabaya - Masruroh, Sayidah Afyatul; Mutmainah, Siti; Juanita, Vita; Aziz, Moh Ali; Huda, Sokhi (MUHARRIK: Jurnal Dakwah dan Sosial, 2022)
This article describes the manifestation of religious moderatism in the Surabaya urban multicultural community. This study aims to reveal symbol of religious moderatism, involvement of figures in the practice of religious moderatism, religious rituals, and social values are manifested from the attitude of religious moderatism in the Surabaya urban multicultural community. The results of this study show that the religious tolerance that exists in multicultural and multi-religious communities in Surabaya is reflected in the manifestation of religious moderatism in the form of specific symbols shown by the people of Surabaya in social interaction. In addition, the involvement of community leaders, religious leaders, and regional leaders who work together to strengthen religious moderation also are needed. The attitudes and behaviour of Surabaya people in interacting with the multi-religious community. The Last, namely the form of values that appear in the civilized, balanced, tolerant behaviour of Surabaya people, deliberation, prioritizing priorities, spreading peace, dynamic and innovative, firm, the principle of equality, always taking the middle way or wasathiyyah. This study argues that the synergy of all parties plays an essential role in the growth, preservation, and development of religious moderatism in a multicultural metropolitan society.